Openwater fisheries of Bangladesh - Tsai, Chu-fa.; Ali, M. Youssouf (Muhammad Youssouf); Bangladesh Centre for Advanced Studies (Dhaka, Bangladesh : Published for Bangladesh Centre for Advanced Studies, University Press Ltd., 1997)
Contributed articles.
Includes bibliographical references.
Keywords: Fisheries -- Bangladesh